An Implementation Methodology for Process Management in Public Organizations - Brodbeck, Angela Freitag; Hoppen, Norberto; Bobsin, Debora (Revista de Administração da UFSM, 2017)
Organizations are embedded in an economic and social complex environment. In order to qualify their outcomes, they continuously search for new management practices. Process Management is one of these practices. Its goal is to integrate processes, people and technology in order to increase the quality of services (and products) produced. Process Management influences organizational structures and management, and it requires a clear understanding of what makes the organization work well. In this context, our study aims to develop a methodology to implement Process Management in public organizations. These organizations are subject to requirements to improve strategies and processes to manage and foster accountability to citizens who use their services. In order to achieve the proposed objective, we adopted the design research method, applied to two case studies. The methodology we structured is based on conceptual models and consists of steps supported by management tools. Our main contributions are the structuration and evaluation of a Process Management methodology adapted for public organizations and the description of the adoption of design research in research concerning processes and its management.